TEKNIK PEWAWANCARA PROGRAM SIARAN TELEVISI WIRASA DALAM MENGENDALIKAN WAWANCARA - I Gusti Ngurah Aan Darmawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Broadcast programs have become important factors for the television industry to win the competition in the digital broadcasting era. Talk shows are one type of broadcast program that can be found on television by viewers. The interviewer becomes an important actor in the success of the talk show broadcast program. The interviewer must have expertise in asking questions as well as controlling the interview so that the broadcast program delivered is not only interesting but also beneficial for the viewers. The theories used in this study were conversation rules and patterns of controlling interviews. This study was conducted in a qualitative method with a case study approach to the interviewers of Wirasa broadcast program aired on the Public Broadcasting Institution (Lembaga Penyiaran Publik TVRI Stasiun Bali). The data were collected through interviews, observations, and document analysis. The results of the research showed that the technique used by interviewers in Wirasa program in controlling the interview went through various stages of exposition, complication, rising action, turning point, and ending. Meanwhile, in managing the conversation, the interviewer exercised control by giving a fair portion for the interviewee to answer.